Whole-genome sequencing of Proteus mirabilis strain CM018 isolated from retail chicken meat - Tan, H.K; Nurzafirah Mazlan; Rinai k; Thung, T.Y (Rynnye Lyan Resources, 2025)
In this study, Proteus mirabilis strain CM018 was isolated from retail chicken meat and confirmed by 16S rRNA gene sequencing. Whole-genome sequencing (WGS) was performed using a combination of Illumina and Oxford Nanopore Technologies (ONT), followed by hybrid assembly and polishing tools. The genome has 3,812,096 bp and 3342 protein coding sequences with GC content of 38.6%. Antibiotic resistance genes (ARGs) such as Tet(J), Cata, crp, and 3 CRISPR arrays were found in the genome. Additionally, antiviral defense systems of Gabija, PARIS, PD-Lamda-5 and Septu were detected using the webserver PADLOC and Defense Finder. Further, experimental results showed that a siphoviridae prophage was isolated using mitomycin C induction. The findings contribute to the understanding of P. mirabilis in retail chicken meat and its potential to pose a substantial public health threat.